Nanorings with copper(ii) and zinc(ii) centers: forcing copper porphyrins to bind axial ligands in heterometallated oligomers - Cremers, J; Richert, S; Kondratuk, D; Claridge, T; Timmel, C; Anderson, H (Royal Society of Chemistry, 2016)
The affinity of copper(ii) porphyrins for pyridine ligands is extremely weak, but oligo-pyridine templates can be used to direct the synthesis of Cu-containing cyclic porphyrin oligomers when they also have Zn centers. We report the synthesis of two heterometallated nanorings: a six-porphyrin ring prepared from a Zn/Cu/Zn linear trimer and a ten-porphyrin ring prepared from a Zn/Zn/Cu/Zn/Zn pentamer. Both these macrocycles have copper porphyrins at two specific positions across the diameter of the ring and zinc at other sites. The presence of a paramagnetic metal results in broadening of the 1H NMR spectra and reduces the relaxation time constants (T1 and T2). The changes in T1 provide quantitative information on the distance of each proton from the copper atom. The Zn/Zn/Cu/Zn/Zn linear porphyrin pentamer binds strongly to a penta-pyridyl template, despite the weakness of the Cu-N interaction, because of the chelate cooperativity of the neighboring Zn-N coordination. The stabilities of a family of four linear porphyrin pentamer complexes were determined by UV-vis-NIR titration and analyzed using a chemical double-mutant cycle. The results show that the free energy of interaction of a copper center to axial pyridine ligands is -6.2 kJ mol-1 when the entropy cost of bringing together the two molecules has already been paid by pyridine-zinc interactions. The development of template-directed approaches to the synthesis of nanorings with combinations of different metals at specific positions around the ring opens up many possibilities for controlling the photophysical behavior of these supramolecular systems and for probing their conformations by EPR.